2009
DOI: 10.2353/ajpath.2009.090417
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds Prevent Alzheimer’s Pathology through Different Effects on the Amyloid-β Aggregation Pathway

Abstract: Inhibition of amyloid-␤ (A␤) aggregation is an attractive therapeutic strategy for Alzheimer's disease (AD). Certain phenolic compounds have been reported to have anti-A␤ aggregation effects in vitro.This study systematically investigated the effects of phenolic compounds on AD model transgenic mice (Tg2576). Mice were fed five phenolic compounds (curcumin, ferulic acid, myricetin, nordihydroguaiaretic acid (NDGA), and rosmarinic acid (RA)) for 10 months from the age of 5 months. Immunohistochemically, in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
278
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(290 citation statements)
references
References 76 publications
(100 reference statements)
8
278
1
3
Order By: Relevance
“…18) If each mouse is assumed to take about 3-4 g of chow (containing 0.5% ferulic acid) per day, the ferulic acid dose is around 500-667 mg/kg/d, 18) which about 95-125 fold higher than the dose of 5.3 mg/kg/d used in the present study. Thus, the reason for the lack of ferulic acid effect on Aβ diposition in Hamaguchi et al 18) most probably could be due to the use of an inappropriately high dose. It is to be noted that curcumin, an analogue of ferulic acid, has also been reported to decrease amyloid deposition and Il-1β levels in the brain of APP transgenic mice at a low dose but not at a high dose.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…18) If each mouse is assumed to take about 3-4 g of chow (containing 0.5% ferulic acid) per day, the ferulic acid dose is around 500-667 mg/kg/d, 18) which about 95-125 fold higher than the dose of 5.3 mg/kg/d used in the present study. Thus, the reason for the lack of ferulic acid effect on Aβ diposition in Hamaguchi et al 18) most probably could be due to the use of an inappropriately high dose. It is to be noted that curcumin, an analogue of ferulic acid, has also been reported to decrease amyloid deposition and Il-1β levels in the brain of APP transgenic mice at a low dose but not at a high dose.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it has been reported that chronic administration of ferulic acid did not affect Aβ diposition in the brain of APP/PS1 mice. 18) These mice were fed with chow containing 0.5% ferulic acid for 1 year (from the age of 4 months to 14 months). 18) If each mouse is assumed to take about 3-4 g of chow (containing 0.5% ferulic acid) per day, the ferulic acid dose is around 500-667 mg/kg/d, 18) which about 95-125 fold higher than the dose of 5.3 mg/kg/d used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wine-derived phenolic compounds, and particularly resveratrol, have been shown be cerebro-or neuroprotective in various models, in vitro and in vivo, and potential mechanisms have been proposed. Data from similar studies using different varieties of red wines with different profiles of phenolic compounds, as well as studies comparing different phenolic compounds, suggest that the individual classes of phenolic compounds may exhibit differential effects in the brain [98,99]. From Scholey et al (2014), the consumption of 100 mL of red wine with a relatively low concentration of resveratrol resulted in better performance by elderly subjects during Series Threes of Cognitive Demand Battery tests, compared with consumption of that same wine enriched with 100 mg resveratrol, while the resveratrol-enriched red wine resulted in better performance during Serial Sevens [155].…”
Section: Potential Biological Mechanisms Of Action For Ethanol and Wimentioning
confidence: 99%
“…Additionally, the use of compounds or extracts inhibiting Aβ aggregation is considered a good approach to the therapy and prevention of AD. For example, flavonoids such as myricetin, quercetin, and kaempferol inhibited Aβ aggregation (exhibited antiamyloidogenic activities) [12][13][14]. Additionally, rosmarinic acid and curcumin are other compounds that inhibit Aβ aggregation efficiently [15,16].…”
Section: Discussionmentioning
confidence: 99%